Sustainable Cleft Care Through Education: The First Simulation-Based Comprehensive Workshop in the Middle East and North Africa Region. (July 2019) - Kantar, Rami S.; Ramly, Elie P.; Almas, Fernando; Patel, Krishna G.; Rogers-Vizena, Carolyn R.; Roche, Nathalie A.; Zgheib, Elias; Munoz-Pareja, Jennifer C.; Nader, Marie K.; Kummer, Ann W.; Flores, Roberto L.; Van Aalst, John A.; et al.
Objective: To describe the conduct of the first multidisciplinary simulation-based workshop in the Middle East/North Africa region and evaluate participant satisfaction. Design: Cross-sectional survey-based evaluation. Setting: Educational comprehensive multidisciplinary simulation-based cleft care workshop. Participants: Total of 93 workshop participants from over 20 countries. Interventions: Three-day educational comprehensive multidisciplinary simulation-based cleft care workshop. Main Outcome Measures: Number of workshop participants, number of participants stratified by specialty, satisfaction with workshop, number of workshop staff, and number of workshop staff stratified by specialty. Results: The workshop included 93 participants from over 20 countries. The response rate was 47.3%, and participants reported high satisfaction with all aspects of the workshop. All participants reported they would recommend it to colleagues (100.0%) and participate again (100.0%). No significant difference was detected based on participant specialty or years of experience. The majority were unaware of other cleft practitioners in their countries (68.2%). Conclusion: Multidisciplinary simulation-based cleft care workshops are well received by cleft practitioners in developing countries, serve as a platform for intellectual exchange, and are only possible through strong collaborations. Advocates of international cleft surgery education should translate these successes from the regional to the global arena in order to contribute to sustainable cleft care through education.